2021
DOI: 10.3389/fphys.2021.721381
|View full text |Cite
|
Sign up to set email alerts
|

A Physio-Logging Journey: Heart Rates of the Emperor Penguin and Blue Whale

Abstract: Physio-logging has the potential to explore the processes that underlie the dive behavior and ecology of marine mammals and seabirds, as well as evaluate their adaptability to environmental change and other stressors. Regulation of heart rate lies at the core of the physiological processes that determine dive capacity and performance. The bio-logging of heart rate in unrestrained animals diving at sea was infeasible, even unimaginable in the mid-1970s. To provide a historical perspective, I review my 40-year e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…We recently demonstrated the utility of CW-NIRS in voluntarily diving seals and breath-hold diving humans performing deep dives (>100 m) ( McKnight et al, 2019 , 2021a , b ). Thus, this technology promises to open new avenues for physiological research in free-ranging animals, as highlighted in a number of recent physio-logging reviews ( Fahlman et al, 2021a ; Ponganis, 2021 ; Williams et al, 2021 ; Williams and Hindle, 2021 ; Williams and Ponganis, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated the utility of CW-NIRS in voluntarily diving seals and breath-hold diving humans performing deep dives (>100 m) ( McKnight et al, 2019 , 2021a , b ). Thus, this technology promises to open new avenues for physiological research in free-ranging animals, as highlighted in a number of recent physio-logging reviews ( Fahlman et al, 2021a ; Ponganis, 2021 ; Williams et al, 2021 ; Williams and Hindle, 2021 ; Williams and Ponganis, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The larger diameter purkinje fibres gave recovery times of order 2000 ms. All these values could be compared with resting and exercising heart rates amongst mammalian species. For example, resting heart rates of blue whale ∼30; elephant, ∼30; human, ∼70; mouse, ∼650; shrew, ∼835, Etruscan shrew, ∼1,511 bpm, correspond to cardiac cycle durations of ∼2000, ∼2000, ∼850, ∼90, ∼70 and ∼40 ms respectively ( Benedict and Lee, 1936 ; Fons et al, 1997 ; Ho et al, 2011 ; Goldbogen et al, 2019 ; Ponganis, 2021 ). Electrodiffusion could thus potentially either entirely, or partially but significantly, account for such recovery in atrial and ventricular cardiomyocytes respectively, to extents dependent on the species heart rates.…”
Section: Discussionmentioning
confidence: 99%
“…Research on cetaceans found that when whales dive, they can reduce their heart rate (bradycardia) to 4–8 beats per minute (bpm) and increase it to 40 bpm at the surface (tachycardia) [ 43 ]. Emperor penguins have a similar diving response, where their heart rate is reduced to 5–10 bpm at the bottom of the ocean, from 200–240 bpm at the sea surface [ 44 ]. Since blood pressure is associated with elevated IOP in humans, this might be one of the possible mechanisms in marine mammals and seabirds to reduce IOP while diving underwater with a high atmospheric pressure.…”
Section: Discussionmentioning
confidence: 99%